Silica-coated flexible liposomes as a nanohybrid delivery system for enhanced oral bioavailability of curcumin - Li C (Dove Medical Press, 2012)
Chong Li, Yan Zhang, Tingting Su, Lianlian Feng, Yingying Long, Zhangbao ChenKey Laboratory on Luminescence and Real-Time Analysis, Ministry of Education, College of Pharmaceutical Sciences, Southwest University, Chongqing, ChinaAbstract: We investigated flexible liposomes as a potential oral drug delivery system. However, enhanced membrane fluidity and structural deformability may necessitate liposomal surface modification when facing the harsh environment of the gastrointestinal tract. In the present study, silica-coated flexible liposomes loaded with curcumin (CUR-SLs) having poor water solubility as a model drug were prepared by a thin-film method with homogenization, followed by the formation of a silica shell by the sol-gel process. We systematically investigated the physical properties, drug release behavior, pharmacodynamics, and bioavailability of CUR-SLs. CUR-SLs had a mean diameter of 157 nm and a polydispersity index of 0.14, while the apparent entrapment efficiency was 90.62%. Compared with curcumin-loaded flexible liposomes (CUR-FLs) without silica-coatings, CUR-SLs had significantly higher stability against artificial gastric fluid and showed more sustained drug release in artificial intestinal fluid as determined by in vitro release assays. The bioavailability of CUR-SLs and CUR-FLs was 7.76- and 2.35-fold higher, respectively, than that of curcumin suspensions. Silica coating markedly improved the stability of flexible liposomes, and CUR-SLs exhibited a 3.31-fold increase in bioavailability compared with CUR-FLs, indicating that silica-coated flexible liposomes may be employed as a potential carrier to deliver drugs with poor water solubility via the oral route with improved bioavailability.Keywords: silica, flexible liposome, oral bioavailability, curcumin